1991
DOI: 10.1159/000226955
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic Effect of Force-Feeding an Extract of Black Pepper <i>(Piper nigrum) </i>in Egyptian Toads <i>(Bufo regularis)</i>

Abstract: 50 male and 50 female Bufo regularis were treated, by force-feeding, with an extract of black pepper, at a dose level of 2 mg, 3 times a week for 5 months. The first tumors appeared after 2 months. Liver tumors (hepatocellular carcinomas, lymphosarcomas and fibrosarcomas) were found in 12 males and 18 females. Metastatic deposits of hepatocellular carcinomas were registered in the spleen, kidney, fat body and ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For instance, piperine, a major chemical compound present in black pepper, has shown anti-inflammatory, anti-angiogenic, and anti-arthritic effects [15]. Moreover, it has been reported that black pepper is capable to reduce breast cancer cell proliferation [1618]. Turmeric is an abundant medicinal herb majorly cultivated in Asia and is widely used in food industries as a colouring agent or food additive [19].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, piperine, a major chemical compound present in black pepper, has shown anti-inflammatory, anti-angiogenic, and anti-arthritic effects [15]. Moreover, it has been reported that black pepper is capable to reduce breast cancer cell proliferation [1618]. Turmeric is an abundant medicinal herb majorly cultivated in Asia and is widely used in food industries as a colouring agent or food additive [19].…”
Section: Introductionmentioning
confidence: 99%